Properties of Micro-Arc Oxidation Coating Fabricated on Magnesium Under Two Steps Current-Decreasing Mode - Wang, Ze-Xin; Zhang, Jin-Wei; Ye, Fei; Lv, Wei-Gang; Lu, Sheng; Sun, Lei; Jiang, Xi-Zhi (Frontiers in Materials, 2020)
A concept of two steps current-decreasing mode derived from constant current mode was developed to fabricate micro-arc oxidation (MAO) coatings on ZK60 Magnesium (Mg) alloy in a dual electrolyte system. The growth characteristics of coatings were analyzed by voltage-time curves, and the coating microstructures were characterized by scanning electron microscopy (SEM). Meanwhile, the roughness, corrosion behavior and microhardness of MAO coatings were investigated. The results showed that the MAO coatings exhibit a smooth and compact surface and have improved hardness and thickness, smaller roughness, uneven distribution of holes and even low electrical energy consumption. Such positive characteristics results in an improved corrosion resistance of MAO coatings. The coating produced under the two steps current mode of “1.2-0.6A” showed a smaller corrosion rate of 0.1559 g/m2h as compared to the counterpart produced under the other modes. The nanoscratch tests results showed that the coating fabricated by “1.2-0.6A” mode has strong bond strength with the substrate. Under this optimized mode, the MAO process also had the lowest energy consumption of 49.8 W·(dm2·μm)-1.